The Implementation of Using Duolingo a nd Elsa Speak Application Towards Students’ Speaking Ability of Eighth Grade at SMP Negeri 2 Wamena - Esraweddi Siregar; Lastri Wahyuni Manurung; Sondang Manik (Journal of Language Education (JoLE), 2025)
The purpose of this study was to Know the improvement of students through Duolingo application on speaking, to know the improvement of students through Elsa Speak Application and to know which application is better to improve speaking ability at SMP Negeri 2 Wamena. This research used Classroom Action Research (CAR). The population of this research is students of SMP Negeri 2 Wamena. The sample of the research was grade VIII A and the total of them was 30. This research used two cycles namely cycle I and cycle II and every cycle had four steps namely planning, implementing, observing and reflecting. The observation was analyzed qualitatively, the test was analyzed quantitatively. In cycle I using the Duolingo application the students mean score was 71.3, while mean score of the students' in cycle II was 85. It can be concluded that the Duolingo application improved the students' ability in speaking students learning outcomes improve. In cycle I using the Elsa Speak application the students mean score was 67.3, while mean score of the students' in cycle II was 83.3. It can be concluded that the Elsa Speak application improved the students' ability in speaking students learning outcomes improve. teaching speaking using Duolingo was more significant in increasing students' speaking than the Elsa Speak application. This is proven by the average score in the second cycle for the class taught by Duolingo, which was 85. Meanwhile, the class taught with the Elsa Speak application had an average score of 83.3.